2014
DOI: 10.1097/phh.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

Current and Planned Shared Service Arrangements in Wisconsin Local and Tribal Health Departments

Abstract: There is widespread use of shared services among health departments in Wisconsin. Extensive qualitative comments suggest participant satisfaction with what the arrangements have accomplished. Motivating factors in developing the arrangements and limited mention of expiration dates suggest continued study of how these arrangements may evolve. Further examination of shared services as a potential mechanism to advance service effectiveness and efficiency is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…3 A 2012 study in Wisconsin found that 71% of LHDs (including tribal health departments) reported sharing services with one or more other LHDs. 5 That study also found that CJS was: more prevalent in areas with smaller populations, most frequently focused on emergency preparedness and environmental health activities, and motivated by interests in making better use of resources, responding to program requirements, and providing better services. The higher prevalence of CJS in Wisconsin compared to national data may be explained in part by prior experience with regional emergency preparedness consortia, state statutes that allow for sharing of services, or the large number of LHDs that serve smaller populations.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…3 A 2012 study in Wisconsin found that 71% of LHDs (including tribal health departments) reported sharing services with one or more other LHDs. 5 That study also found that CJS was: more prevalent in areas with smaller populations, most frequently focused on emergency preparedness and environmental health activities, and motivated by interests in making better use of resources, responding to program requirements, and providing better services. The higher prevalence of CJS in Wisconsin compared to national data may be explained in part by prior experience with regional emergency preparedness consortia, state statutes that allow for sharing of services, or the large number of LHDs that serve smaller populations.…”
Section: Introductionmentioning
confidence: 88%
“…1 Information about the questionnaire was previously reported. 5 The definition of CJS provided to participants was: Sharing of resources (such as staffing or equipment or funds) on an ongoing basis. The resources could be shared to support programs (like a joint WIC or environmental health program) or organizational functions (such as human resources or information technology).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 It exists across all public health program areas, service sharing, and governance structures. 7,8 In a climate of insufficient resources, LHD are implementing alternative strategies to providing services represented by an overall national increase in CJS. 1,4,6…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The opportunities to solve problems of financial instability by reducing the cost-of-service delivery for Kentucky's LHJs, via CJS, present a mechanism to achieve economies of scale, especially among smaller jurisdictions. [16][17][18] In addition, Humphries et al 16 identified a greater use of nonmandated services (eg, asthma, obesity prevention, healthy food options) among jurisdictions with greater levels of sharing. Thus, CJS presents Kentucky an opportunity to provide LHJ services in both an effective 28 (eg, needed services to a state with many health needs) and an efficient 28 (minimal resource outlay) format.…”
mentioning
confidence: 99%